If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3n + -1) = (4n + 8) + 7 Reorder the terms: 2(-1 + 3n) = (4n + 8) + 7 (-1 * 2 + 3n * 2) = (4n + 8) + 7 (-2 + 6n) = (4n + 8) + 7 Reorder the terms: -2 + 6n = (8 + 4n) + 7 Remove parenthesis around (8 + 4n) -2 + 6n = 8 + 4n + 7 Reorder the terms: -2 + 6n = 8 + 7 + 4n Combine like terms: 8 + 7 = 15 -2 + 6n = 15 + 4n Solving -2 + 6n = 15 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. -2 + 6n + -4n = 15 + 4n + -4n Combine like terms: 6n + -4n = 2n -2 + 2n = 15 + 4n + -4n Combine like terms: 4n + -4n = 0 -2 + 2n = 15 + 0 -2 + 2n = 15 Add '2' to each side of the equation. -2 + 2 + 2n = 15 + 2 Combine like terms: -2 + 2 = 0 0 + 2n = 15 + 2 2n = 15 + 2 Combine like terms: 15 + 2 = 17 2n = 17 Divide each side by '2'. n = 8.5 Simplifying n = 8.5
| 2.00-.33=.22x | | 2t+6=21-t | | 5(5x+2)-9=25x+1 | | 8c=90-c | | 11-5y=4y+20 | | 65-5x=4x+23 | | 47x+1673x-15=43(40x+60) | | 11+5y=4y+20 | | 4(t+2)=18-t | | x^2+3x-2x=5x+1 | | .6x-4.2=.6 | | 93-5x=8x-15 | | 4x-2=11x-54 | | -4(3x-1)+7(3-2x)= | | 3(4x+3)+99=17x+4-5x+104 | | 0.5x-6+2x+0.5x=12 | | -118-10x=10x+22 | | 8+6x=2x-32 | | 1/2(x+8)=14 | | 4350-3915=87(50x-45) | | (x-3)/3=x/5 | | 11x+10=7x+2 | | 8x+3+5x-5=180 | | 35=10x+5y-15 | | x/8-5=-22 | | 9x+31x-9=8(5x+7) | | -3(t-2)+5t=4t-1 | | 10x+18=2x-2 | | 2x^2=x^3-x+1 | | 24x-5=6(4x+1) | | 12x-134=2x-14 | | 0.16d+0.6=.25(d-2) |